2006
DOI: 10.1016/j.dnarep.2005.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Closely opposed apurinic/apyrimidinic sites are converted to double strand breaks in Escherichia coli even in the absence of exonuclease III, endonuclease IV, nucleotide excision repair and AP lyase cleavage

Abstract: Multiply damaged sites (MDSs) consist of two or more damages within 20 base pairs (bps) and are introduced into DNA by ionizing radiation. Using a plasmid assay, we previously demonstrated that repair in Escherichia coli generated a double strand break (DSB) from two closely opposed uracils when uracil DNA glycosylase initiated repair. To identify the enzymes that converted the resulting apurinic/apyrimidinic (AP) sites to DSBs, repair was examined in bacteria deficient in AP site cleavage. Since exonuclease I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 44 publications
4
44
0
Order By: Relevance
“…It is interesting to note that, although it would have been especially informative to have conducted TM studies with AP THF in a strain that is deficient in xth nfo nfi and uvrA concurrently, thus compromising all known AP site repair pathways simultaneously, we were unable to construct such a quadruple mutant strain, even when using a P1 stock that produced viable mutants in other backgrounds (Table S1). Together, these results support recent observations that repair of AP sites can occur through another, unknown mechanism in addition to those mediated by AP endonucleases, AP lyases, NER, or Nfi (25). Similarly, the strand breaks are processed in the absence of AP endonucleases, Nfi, and NER.…”
Section: Discussionsupporting
confidence: 78%
“…It is interesting to note that, although it would have been especially informative to have conducted TM studies with AP THF in a strain that is deficient in xth nfo nfi and uvrA concurrently, thus compromising all known AP site repair pathways simultaneously, we were unable to construct such a quadruple mutant strain, even when using a P1 stock that produced viable mutants in other backgrounds (Table S1). Together, these results support recent observations that repair of AP sites can occur through another, unknown mechanism in addition to those mediated by AP endonucleases, AP lyases, NER, or Nfi (25). Similarly, the strand breaks are processed in the absence of AP endonucleases, Nfi, and NER.…”
Section: Discussionsupporting
confidence: 78%
“…In general, opposing lesions were converted to SSBs if they were positioned ≥ 3 bps apart. Work in bacteria and mammalian cells has shown similar results with respect to AP sites or the furan abasic site analog, and has demonstrated that opposing lesions can be converted to DSBs in cells (15; 23). Interestingly, studies examining closely opposed base damage in bacteria have shown that the lesions are not converted to DSBs, but rather enhance mutation frequency at the individual lesions in the cluster (2427).…”
Section: Introductionmentioning
confidence: 82%
“…As a consequence, nucleotides can be oxidized (such as guanine to 8-oxoG) resulting in base transversion (GC-TA), abasic sites and DNA single-and double-strand breaks. (7)(8)(9)(10)(11)(12) For cellular integrity, DNA double-strand breaks (DSB) can be fatal and their repair is initiated by the cellular DNA damage response (DDR) consisting of a multi-protein signalling cascade. (13,14) An early event in DSB response is phosphorylation of the H2A subtype histone H2AX at ser-139 (also known as γH2AX) by the phosphatidylinositol 3-like kinases ATM, ATR and DNA-PK.…”
Section: Introductionmentioning
confidence: 99%